Conserving corridors: an integrated landscape modelling approach to facilitate leopard (Panthera pardus) conservation in the Western Cape, South Africa - Greyling, Eugene (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScConEcol)--Stellenbosch University, 2023.